(untitled) (Homoeopathy for All, 2025)
Dr. Bach believed that disease stems from an imbalance between body and mind, where negative emotions disrupt energy flow, eventually leading to physical symptoms. His alternative medicine approach aims to clear away emotions like fear, worry, anger, self doubt, indecision, sadness, impatience, and guilt, gently reestablishing harmony between mind and body, which allows natural healing to take place. There are 38 Bach flower remedies, with 37 derived from specific flowers and tree blossoms and one from natural spring water, each offering unique healing benefits.